2020
DOI: 10.1002/ece3.6788
|View full text |Cite
|
Sign up to set email alerts
|

Burrow ambient temperature influences Helice crab activity and availability for migratory Red‐crowned cranes Grus japonensis

Abstract: For migratory birds that specialize on particular benthic macroinvertebrate species, the timing of migration is critical since prey availability may be temporally limited and a function of local ambient temperature. Hence, variation in local ambient temperature can influence the diet composition of migrant birds, and, consequently, they may be constrained by which stopover and wintering sites they are able to utilize during periods of colder temperatures. Here, we use fecal analysis, observer‐based population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Meanwhile, crab burrow density in the vegetated areas during the warm seasons was higher than in cold seasons. With temperature rising, crabs move to vegetated areas to decrease the risk of exposure to high thermal and predation stresses rises (Stone and O'Clair, 2001;Morris, 2005;Walther et al, 2009;Li et al, 2020;Andreo-Martıńez et al, 2021). The mean value of median grain size in the marsh area was similar to the mean value in un-vegetated area.…”
Section: Discussionmentioning
confidence: 76%
“…Meanwhile, crab burrow density in the vegetated areas during the warm seasons was higher than in cold seasons. With temperature rising, crabs move to vegetated areas to decrease the risk of exposure to high thermal and predation stresses rises (Stone and O'Clair, 2001;Morris, 2005;Walther et al, 2009;Li et al, 2020;Andreo-Martıńez et al, 2021). The mean value of median grain size in the marsh area was similar to the mean value in un-vegetated area.…”
Section: Discussionmentioning
confidence: 76%
“…However, we found that there was a higher density of tidal crabs during the autumn stopover but with much lower vigilance investment, and at our study site, the effect of crab availability, rather than density on vigilance seems to have been more important. However, the availability of crabs for other threatened migrants such as Red-crowned Cranes (Grus japonensis) is largely determined by burrowing ambient temperature which varies depending on time of day and season (Li et al 2020b) and future studies should consider the influence of ambient temperature on curlew vigilance through its effects on prey availability.…”
Section: Discussionmentioning
confidence: 99%
“…At the cost of losing potential protective functions of vegetation, on the non-vegetated mudflats these birds can maintain a highly efficient anti-predator or anti-competitor vigilance by monitoring the environment without visual obstruction (Beauchamp 2014). At many shorebird stop-over sites, saltmarsh vegetation also forms a considerable landscape component adjacent to mudflats (Hao et al 2017;Lu et al 2018;Xing and Xing 2019) and attract large numbers of waterbirds foraging on abundant microbenthic and other prey species (Zhang et al 2016(Zhang et al , 2021Li et al 2020b). Compared to non-vegetated habitats, foraging in saltmarsh vegetation necessitates an adjustment to their vigilance strategy to cope with the potential visual obstruction of the vegetation structure, particularly when birds are "head down" (Metcalfe 1984;Li et al 2017).…”
mentioning
confidence: 99%
“…S. salsa saltmarshes also provide important ecosystem services, such as carbon sequestration("blue carbon"), shoreline protection, and biodiversity maintenance [23,24], and serves as an important foraging and resting habitat for endangered waterbirds that migrate along the EAAF, including the Red-crowned Crane (Grus japonensis) [25,26], the Far Eastern Curlew (Numenius madagascariensis), and the Great Knot [22,27]. However, S. salsa saltmarshes also face serious threats from reclamation, lower runoff of river discharge, uncontrolled tourist development, oil exploitation, invasive species, and sea-level rise [8,24].…”
Section: Introductionmentioning
confidence: 99%